2014
DOI: 10.2217/fon.13.198
|View full text |Cite
|
Sign up to set email alerts
|

Brooke–Spiegler Syndrome Tumor Spectrum Beyond the Skin: A Patient Carrying Germline R936X CYLD Mutation and a Somatic CYLD Mutation in Brenner tumor

Abstract: Brooke-Spiegler syndrome is a hereditary disorder characterized by a predisposition to the development of skin appendage neoplasms and the major and minor salivary glands neoplasms. The role of the CYLD mutation in visceral neoplasms is still unclear, except for the parathyroid tumor. We report the case of a 46-year-old patient with multiple cylindromas and trichoepitheliomas, a Brenner tumor of the ovary and a negative family history for Brooke-Spiegler phenotype. Genetic analysis revealed R936X germline muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Moreover, our patient did not present additional visceral tumours or diseases related to BSS. 58 The overall phenotype of our patient may support the hypothesis that somatic mutations in adjunct to CYLD germline mutations play a central role in the development of the tumour phenotype and in the genotype-phenotype correlations although it is not always necessary with tumour suppressors to have two mutations. However, large case studies are required in order to verify this hypothesis and clarify the impact of somatic mutations on the expression of the distinct syndromic phenotype that may vary from disfiguring clinical aspects to attenuated forms.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, our patient did not present additional visceral tumours or diseases related to BSS. 58 The overall phenotype of our patient may support the hypothesis that somatic mutations in adjunct to CYLD germline mutations play a central role in the development of the tumour phenotype and in the genotype-phenotype correlations although it is not always necessary with tumour suppressors to have two mutations. However, large case studies are required in order to verify this hypothesis and clarify the impact of somatic mutations on the expression of the distinct syndromic phenotype that may vary from disfiguring clinical aspects to attenuated forms.…”
Section: Discussionsupporting
confidence: 75%
“…A total of 93 germline mutations in CYLD gene have been identified so far . 57,58 These CYLD mutations have been most frequently identified in the C-terminal region of the gene (from 9 to 20 exon). 59 CYLD is widely expressed and regulates a myriad of cell functions including inflammation and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Somatic mutations have been found in BRAF and N-RAS genes in about 50% and 20% of melanomas, respectively, resulting in constitutive activation of ERK1/2 MAPK pathway. 16 Moreover, gene expression profiling and targeted approaches have demonstrated that ETB expression is upregulated in melanoma. 12,17 The upregulation of ETB is involved in proliferation, migration and angiogenesis associated with tumor growth and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Ponti and colleagues recently reported an ovarian Brenner tumor positive for a CYLD mutation in a BSS patient. 6 So far there are no curative therapies for the skin lesions of BSS. Various ablative and non-ablative techniques have been used with variable results.…”
Section: 3810mentioning
confidence: 99%
“…This probably reflects the physiological importance and ubiquity of CYLD protein expression. 1,5,6 Despite the growing number of mutations reported over the last decade, there is no defined genotype-phenotype correlation in BSS. 1,3,7 We describe two members of a family affected by multiple nodular scalp lesions, present for decades and with clinical and histological features consistent with BSS and confirmed after identification of a new germline mutation of CYLD gene.…”
Section: Introductionmentioning
confidence: 99%